Miss Bindergarten celebrates the 100th day of kindergarten - Slate, Joseph (Dutton Children's Books, 1998)
To celebrate one hundred days in Miss Bindergarten's kindergarten class, all her students bring one hundred of something to school, including a one hundred-year-old relative, one hundred candy hearts, and one hundred polka dots.